Magnetism in quasi-low-dimensional systems investigated with muon spin rotation and high magnetic fields - Franke, I (2011)
This thesis presents the investigation of magnetism in a selection of low-dimensional systems and its relation to other physical properties, such as superconductivity. The techniques employed are muon spin rotation and pulsed magnetic field magnetisation. The ability of muons to directly probe the local field is used to study SrFeAsF, which is a parent compound of the high-temperature superconducting pnictides. This revealed that the magnetic and structural transitions are separated in this system. I then demon- strate the coexistence of magnetism and superconductivity in NaFeAs for the first time. This discovery is of great interest since the interplay between magnetism and supercon- ductivity is thought to play an important role for high-temperature superconductivity. I further investigate the effect of partially replacing Fe with Co in NaFeAs. I study the ordering and spin reorientation in the Mott insulator Sr₂IrO₄, which has been suggested as a possible high-temperature superconductor. The complex magnetism observed in this system is contrasted to that in related iridates Ca₄IrO₆, Ca₅Ir₃O₁₂ and Sr₃Ir₂O₇. By combining pulsed-field magnetization and low magnetic field experiments with μSR on a series of coordination polymers. I am able to determine the size and direction of the magnetic exchange interaction. I demonstrate how it is possible to adjust the in- teractions by altering the molecular architecture of these Cu-based spin- 1 2 compounds. This is a significant contribution since it will lead to the targeted design of magnetic systems that can be utilized to experimentally test fundamental theories of magnetism.